Technologies for managing political processes in the youth policy of the region - O. N. Blinnikova; N. N. Pachina; A. R. Pachin (Современная наука и инновации)
The article reveals the main directions of youth policy, defines strategies for the implementation of youth policy, describes technologies for managing political processes in the youth policy of the region.